(untitled) (World Bulletin of Public Health, 2023)
In the course of the study, the authors developed a treatment and diagnostic algorithm of actions in the prevention, timely diagnosis and treatment of this contingent, including some tactical and technical aspects, which, in general, made it possible to optimize surgical tactics. A comparative analysis of the results of surgical treatment of urgent surgical interventions in destructive forms of ACC against the background of obesity showed that over the subsequent similar period of time, the incidence and development of postoperative BL decreased from 43 (4.7%) to 29 (2.3%), the frequency of performing relaparotomies decreased from 30 (3.3%) to 10 (0.8%) and deaths from 8 (0.9%) to 0.1%.